2013
DOI: 10.1371/journal.pone.0060994
|View full text |Cite
|
Sign up to set email alerts
|

Baseline Gene Expression Signatures in Monocytes from Multiple Sclerosis Patients Treated with Interferon-beta

Abstract: BackgroundA relatively large proportion of relapsing-remitting multiple sclerosis (RRMS) patients do not respond to interferon-beta (IFNb) treatment. In previous studies with peripheral blood mononuclear cells (PBMC), we identified a subgroup of IFNb non-responders that was characterized by a baseline over-expression of type I IFN inducible genes. Additional mechanistic experiments carried out in IFNb non-responders suggested a selective alteration of the type I IFN signaling pathway in the population of blood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…These data indicate that single risk genes involved in IFN signaling may be dysregulated in MS, and that this phenomenon is not necessarily conserved throughout all MS stages, raising the hypothesis that Interferome may be characterized by transcriptomic changes specific to disease type. Among several reports indicating transcriptional dysregulation induced by IFN-beta treatment in blood cells of MS patients 10 13 , a couple of studies suggest that expression of some type I IFN regulated genes may be dysregulated at baseline and correlate with biological response to IFN-beta therapy 14 16 . No study has however provided the systematic analysis of Interferome in treatment-naïve MS subjects at distinct stages of disease.…”
Section: Discussionmentioning
confidence: 99%
“…These data indicate that single risk genes involved in IFN signaling may be dysregulated in MS, and that this phenomenon is not necessarily conserved throughout all MS stages, raising the hypothesis that Interferome may be characterized by transcriptomic changes specific to disease type. Among several reports indicating transcriptional dysregulation induced by IFN-beta treatment in blood cells of MS patients 10 13 , a couple of studies suggest that expression of some type I IFN regulated genes may be dysregulated at baseline and correlate with biological response to IFN-beta therapy 14 16 . No study has however provided the systematic analysis of Interferome in treatment-naïve MS subjects at distinct stages of disease.…”
Section: Discussionmentioning
confidence: 99%
“…When relative expression levels to VCAM1 were calculated ( VCAM1 is expressed in monocytes (Expression Atlas by EMBL-EBI) and is not differentially expressed between IFNβ-responder and nonresponder RRMS patients 21 ), the data showed that relative mRNA expression of CXCR2 , CXCR1 , and LTBR were significantly higher in IFNβ-responders than nonresponders (Figure 4c). Here, the two-thirds of non-responders showed comparable gene expression levels to responders.…”
Section: Resultsmentioning
confidence: 99%
“…To date, no relevant differences in gene expression have been reproducibly demonstrated in whole blood cells or PBMC when comparing MS patients and controls, patients in clinical relapse and remission, or patients with different disease courses [ 15 21 ]. A higher type-1 IFN signature has been detected in the blood, specifically in monocytes [ 60 , 61 ], of a subset of treatment naïve patients with RRMS and has been associated with a poor response to IFN-β [ 60 , 62 , 63 ]. Recently, differences in PBMC gene expression profiles were detected between male and female patients with RRMS [ 44 ], although results interpretation is complicated by different treatment regimens.…”
Section: Discussionmentioning
confidence: 99%